Preconcentration of Sulfamethoxazole Using a Molecularly Imprinted Polymer (MIP) Prepared by Zeolitic Imidazolate Framework-8 - Hemoglobin Catalyzed by Electrochemically Mediated Atom Transfer Radical Polymerization with Electrochemical Determination on a Screen-Printed Electrode. (11th February 2020) - Zhao, Xiaoya; Wang, Peng; Ye, Cheng; Wang, Han; Cao, Wei
Abstract: A novel approach was developed to prepare molecularly imprinted polymer (MIP) composites on filter paper and with the subsequent determination of sulfamethoxazole in food samples. Hemoglobin was firstly encapsulated in a metal-organic framework to improve its stability and catalytic performance. This mixture was modified with an initiator and immobilized in the paper to prepare the MIP using electrochemically mediated atom transfer radical polymerization. This composite exhibited excellent adsorption capacity (60.1 mg g −1 ) and rapid kinetics, which were better than those of previously reported MIPs. Using the optimized conditions, this MIP composite directly extracted the sulfamethoxazole from complex food samples and was placed on the surface of a screen-printed electrode to quantify sulfamethoxazole with a detection limit of 0.7 ng mL −1 . Sulfamethoxazole recoveries ranged from 99.4 to 103.7% and the results were in good agreement with those obtained by a liquid chromatography – mass spectrometry (LC-MS) method (r = 0.992). This approach may also be applied for the determination of other target molecules.